2015
DOI: 10.1136/bjophthalmol-2015-307326
|View full text |Cite
|
Sign up to set email alerts
|

Macular nerve fibre and ganglion cell layer changes in acute Leber's hereditary optic neuropathy

Abstract: AimsTo evaluate longitudinal retinal ganglion cell inner plexiform layer (GC-IPL) and macular retinal nerve fibre layer (mRNFL) thickness changes in acute Leber's hereditary optic neuropathy (LHON).MethodsSix eyes of four patients with LHON underwent SD-OCT (optical coherence tomography) at month 1, 3, 6 and 12 after visual loss. In two eyes, the examination was carried out in the presymptomatic stage. The relationship and curves for area under the receiver operator characteristic (AUROC) were generated to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 23 publications
9
55
2
6
Order By: Relevance
“…The natural history of peripapillary RNFL changes throughout the different LHON phases has been quantitatively described81819. Our study confirmed a thickening occurring in RNFL layer inferior-temporally, in LHON mutation carriers.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The natural history of peripapillary RNFL changes throughout the different LHON phases has been quantitatively described81819. Our study confirmed a thickening occurring in RNFL layer inferior-temporally, in LHON mutation carriers.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, SD-OCT has been instrumental in the qualitative and quantitative assessment of funduscopic changes over the natural history of LHON81819. Nevertheless, OCT studies have been focused on measuring RNFL and RGC thickness, whereas the vascular changes remained neglected and poorly evaluated.…”
mentioning
confidence: 99%
“…This study reveals significant peripapillary microvascular changes over the different stages of disease progression in patients affected by LHON. The changing pattern of RNFL and GC‐IPL is consistent with previous works . The key finding is that microvascular changes in the temporal sector, implicating the papillomacular bundle, precede the RNFL and mirror the GC‐IPL changes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in patients presenting with first eye involvement, the macular ganglion cell and inner plexiform layer (GC-IPL) and the macular RNFL already showed pathological thinning in the presymptomatic stage about 6 weeks before the onset of visual loss in the fellow eye. Maximal GC-IPL thinning was reached by 6 months and this OCT parameter could, therefore, prove to be a more sensitive biomarker of optic nerve damage compared with peripapillary RNFL measurements where progressive thinning continues until at least 12 months after the first onset of visual loss [14]. …”
Section: Neurodegeneration: In Vivo Imagingmentioning
confidence: 99%